Монгол шүлэг дэх хоёр ба дөрвөнмөрт шүлгийн бүтэц тогтолцоо: Structure of couplet and quatrain in Mongolian verse - Г., Галбаяр (Mongolian Studies, 2023)
<div class="x1okitfd x6ikm8r x10wlt62 x1mzt3pk xm7lytj xn6708d xwib8y2 x1ye3gou x1n2onr6 x13faqbe xzackxk x1vvs6jl x1p8yz0e x1e72984 x1qxsuse x1pwr4jm xgt0i0e xhiudvi x1ikrcl6 xrlr1mf x13m8g0b x1wea3ti x1pdxsal xgyc039 xza5l1d xcavrb8 x1p4c0ny x5l10my xieozyd x14rr3af x1kx6eu5 x1x824oc x1fefmpr x1a3valx" role="none"> Every strophe of the verse has a unique identity depending on the culture, the thinking, the conducting farms, natural-social situation. Mongolian poetry has a glimpse of the structure of the universe in the context of nomadic civilization in the context of extreme climatic conditions. Mongolian verse is created based on the general structure of the universe which is linked to the nomadic culture developing under the four season with extreme climates. The structure of the strophe of Mongolian verse is usually being created by couplet and quatrain or tercet andsixian. Also, Mongolian people regard that the live is developing in wisdom. Therefore, the couplet of Mongolian verse which is the main part is created by wisdom. So, the number of orthotone and atonic words are balanced to the syllable in Mongolian verse. This couplet is being parallel and irrespective of each other because the couplet verse is symmetry. But the meaning of the verse is going deeply from the first line to next. In the course of historical development of strophe of Mongolian verse is developed and extended from couplet to quatrain. Therefore, the structure of quatrain is very similar to couplet.